Hubungan Frekuensi Salat Tahajud dengan Tekanan Darah pada Lansia Karang Werda di Kabupaten Jember - Dinda Syahva Salshabilla (Fakultas Kedokteran, 2025)
The ageing process is a phase in which the body’s ability to repair and regenerate itself gradually declines, which can increase the stiffness of blood vessels, leading to higher blood pressure. Hypertension is blood pressure in which systolic blood surpasses 140 mmHg and diastolic blood is more than 90 mmHg. This condition can be caused by mental conditions which influence people’s stress level. To manage blood pressure issues in the elderly is through meditation, such as performing Tahajjud prayer. The Tahajjud prayer is thought to aid in stress reduction and contribute to lowering blood pressure. The purpose of this study is to define the relationship between the intensity of Tahajjud prayer and blood pressure in the elderly at the elderly forum in Jember Regency. This is a cross-sectional study, which included a total sample of 189 elderly. The prevalence of hypertension is 59.3%; 55% of them have already performed the Tahajjud prayer, and 45% do not perform the Tahajjud prayer. There is a significant relationship between the intensity of Tahajjud prayer and blood pressure in the elderly forum in Jember Regency.
Reaploud Repository February_Hasyim
Keywords: Tahajjud Prayer; Hypertension; Elderly